Kinetics of Simultaneous Saccharification and Lactic Acid Fermentation Processes - Luo, J.; Xia, L.; Lin, J.; Cen, P.
After pretreatment of corn cob by dilute acid, the lignocellulosic residue was used as raw materials for the simultaneous saccharification and lactic acid fermentation (SSLF). Because of the same optimal temperature and pH requirement as well as the anaerobic condition, the lactic acid fermentation is perfectly compatible with enzymatic hydrolysis of cellulosic materials. In the SSLF processes, the final concentration of lactic acid reached 33.97g/L with a conversion ratio of 79